THE USE OF STORY FACE STRATEGY ON STUDENTS’ WRITING SKILL OF NARRATIVE TEXT - Merisna Situmeang; Afril Ashari Harahap; Gian Nuradela; Yesi Gusman; Salsa Billa (Institut Pendidikan Tapanuli Selatan, 2026)
The aims of this study are: to know out the extent of the application of the story face strategy in teaching the ability to write narrative texts, to know the extent of the students’ ability to write narrative texts before and after using the story face strategy, then to know whether there is any significant effect of using of story face strategy on students’ writing skill of narrative text at the eleventh grade of SMA Negeri 6 Padangsidimpuan. The method used is the one group pre-test post-test experiment with a sample of 33 students (taken through purposive sampling from 303 students). Data was collected through observation and tests. The results show that the application of the Story face strategy reaches 95% (excellent category). The mean score of the students’ writing skill of narrative text before and after using story face strategy were 50.42 (fair to adequate category) and 84.76 (good to excellent category). Then, there is any a significant effect of story face strategy on students’ writing skill of narrative text at the eleventh-grade students of SMA Negeri 6 Padangsidimpuan because the table paired sample t-test pretest and post-test is lower than 0.05 (0.000<0.05), it means that hypothesis (Ha) is accepted.